HASIL BELAJAR DRIBBLE BOLA BASKET DENGAN METODE TUGAS DI SDN 04 SEBETUNG - Nudin, Hansan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to determine the learning improvement of student learning outcomes in learning the method of task dribble a basketball in grade V SDN 4 Sebetung. Forms of research is classroom action research. Subjects were teachers collaborate with Class V grade students of SDN 04 Sebetung Sekadau as many as 20 students. Learning dribble a basketball through the methods the task of providing a positive impact on students and provide a significant improvement over the results dribble a basketball. In the first cycle students are the results of students who completed a total of 11 students or 55%, while students and who have not completed amounted to 9 students, or by 45%, then proceed to the second cycle so that students have the opportunity to repair dribble a basketball with categories complete all the graduating students totaling 20 students and unfinished amounted to 0 or does not exist. Keywords: Dribble Basketball , Method Task